2016
DOI: 10.1177/1094670516666674
|View full text |Cite
|
Sign up to set email alerts
|

Service Provider’s Experiences of Service Separation

Abstract: As more and more technologies are infused into service delivery, service providers must continuously renegotiate the ways in which they understand service delivery across increasingly high-tech, low-touch modalities. This exploratory qualitative study examines what health care service providers experience when offering separated services in the empirical context of telehealth. In-depth phenomenographic interviews sourced across multiple hospital and health care sites revealed that service providers experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
100
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 25 publications
1
100
0
1
Order By: Relevance
“…The case of telephone‐based nursing services, for example, lacking in both presence and visibility with patients, has raised the question of what is considered as “real nursing” (Snooks et al., ). Lack of physical presence, combined with technical and other problems, disrupts patient relationships which contributes to healthcare providers feeling less engaged and hence less accepting of VC (Bradford, Young, Armfield, Herbert, & Smith, ; Green et al., ). Yet, presence in nursing is often poorly conceived (Finfgeld‐Connett, ); frequently situated within a context of physical proximity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case of telephone‐based nursing services, for example, lacking in both presence and visibility with patients, has raised the question of what is considered as “real nursing” (Snooks et al., ). Lack of physical presence, combined with technical and other problems, disrupts patient relationships which contributes to healthcare providers feeling less engaged and hence less accepting of VC (Bradford, Young, Armfield, Herbert, & Smith, ; Green et al., ). Yet, presence in nursing is often poorly conceived (Finfgeld‐Connett, ); frequently situated within a context of physical proximity.…”
Section: Discussionmentioning
confidence: 99%
“…What is shared, and with whom, become less secure with VC, a concern identified in other studies (Bradford et al., ). Medical practitioners share this concern not the least because healthcare staff and patients may not know who is “off screen” during consultations and that a sense of privacy during examinations is not the same as in face‐to‐face consultations (Green et al., ). Further demands include how nurses and midwives take on additional roles to accommodate VC because of gaps in technical and liaison support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We extend the ideas put forth by Green et al . () by illustrating the types of identity work that are essential in coping with tensions that can arise by moving away from a secure, stable, and familiar sense of professional self, due to discretionary technology bootlegging activities. It became evident that our informants’ identity work enabled them to deal with tensions induced by the use of technology that lacked legitimacy in the context of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In his seminal study, Barley (1986) found that the introduction of CT scanner technology and its use transformed radiologists' work routines, identities and roles. Similarly, Green et al (2016) showed how technology use influenced healthcare professionals' transition from a secure, stable, and familiar professional identity as a 'physician' to an insecure, unstable, and unfamiliar role as a tele-health 'technician'. These studies are situated in formal organisation-wide technology setting, where policy, structures and institutional repairs enforce or sanction practice.…”
Section: Introductionmentioning
confidence: 99%